Patriarchy and the subordination of women from a radical feminist point of view - Nína Katrín Jóhannsdóttir 1985- (2009)
In this essay I cover matters concerning patriarchy and its undeniable connection to the subordination of women. My reasoning is from a radical feminist point of view since I blame the patriarchy and its detrimental effects, for women’s position in the world today. Firstly I briefly examine women’s traditional subordination from the beginning and to this day. Likewise I survey the birth of feminism and examine in what ways it has been helpful in women’s battle for equal rights. Secondly, I look at a suppression many people seem to be unwilling to see. This is a suppression connected to the sexualization of the public arena. In this chapter I define what pornography is and why it has the effect of belittling women. Furthermore I examine pornography and the internet and finally I reveal the connection between pornography and rapes. In the third chapter I review the exhibition, use and sale of women’s bodies. I examine the sexualization of young girls in the mass media and establish how the society’s sick ideology has had the effect of turning very young girls into sex-objects in advertisements, on the internet, etc. Moreover I examine concepts like ‘the male gaze’ in the advertisement business and how it is an exemplar of men’s control over women and also reveals their supremacy. In the end I address important issues concerning women’s biggest suppression of all in my opinion. This suppression is connected to prostitution and the trafficking in women and children. I look at the development of these issues, firstly in Iceland and then in the Nordic countries, and examine how these issues are handled.